A comparative analysis of the gasification performances of torrefied and untorrefied bagasse: Influence of feed size, gasifier design and operating variables on gasification efficiency - Anukam, Anthony; Okoh, Omobola; Mamphweli, Sampson; Berghel, Jonas (International Journal of Engineering and Technology, 2018)
This study conducted a comparative assessment of the gasification performances of torrefied and untorrefied bagasse with emphasis on feed size, gasifier design and operating conditions that would influence gasification efficiency. Torrefaction greatly improved the characteristics of bagasse and had significant impact on its gasification performance. The gasifier design parameters studied were throat angle and throat diameter. Temperature of input air and feed input were the gasifier operating conditions examined in the course of the gasification processes of both torrefied and untorrefied bagasse. These parameters were considered the most critical operating parameters that affect gasifier performance and, correlation between the parameters was established in the course of gasification. The results obtained showed higher gasification efficiency for torrefied bagasse in comparison to untorrefied bagasse under varied conditions of gasification, which was attributed mainly to changes in the characteristics of the torrefied material.Â